An A - Z of E L T A dictionary of terms and concepts used in english language teaching - Thornbury, Scott (Oxford Macmillan, 2006)
Clear definitions of the concepts, ideas and terminology of english language teaching, every teacher and teacher trainer needs this book.
Contents, bibliography.
Keywords: English - English; Dictionary; Teaching; Grammar; Teacher trainers